UPAYA MAKSIMAL DALAM PELAKSANAAN BIMBINGAN KONSELING KELOMPOK UNTUK MENINGKATKAN KOMITMEN SISWA MENGIKUTI MATA PELAJARAN MATEMATIKA KELAS VIII-4 DI SMP NEGERI 6 DENPASAR SEMESTER I TAHUN PELAJARAN 2017/2018 - Suriasmini, Ni Nyoman (Widyadari: Jurnal Pendidikan, 2019)
The purpose of this study is to increase student commitment in mathematics learning. This research was conducted in SMP Negeri 6 Denpasar in class VIII-4 semester I of 2017/2018 school year. This research is a classroom action research that aims to find out whether group counseling guidance can increase student commitment in following mathematics subjects. In this study, data such as student commitments and student mathematics learning outcomes data were collected by the method of observation and test methods. Data collected will then be analyzed using descriptive analysis. Based on the results of data analysis, it can be concluded that group counseling guidance can increase students' commitment to take mathematics. This is evident from the results obtained in the first cycle increased 27% from the initial data and the average value of the commitment of the group of 64.77 with good criteria. In cycle II there was an increase in student commitment by 32% from the first cycle and the average value of group commitment by 85.41 with very good criteria. Based on the analysis of mathematics learning achievement test, at the end of the second cycle all students get a test score on learning outcomes above the KKM set by the school.